EFEKTIVITAS BANTUAN LANGSUNG TUNAI DANA DESA DI DESA CIKADU KECAMATAN CIKALONG KABUPATEN TASIKMALAYA - Andi; Yanti Heryanti; Putri Syifa Novia Rahmah (Journal Of Regional Public Administration (JRPA), 2021)
This study aims to determine and analyze the effectiveness of Village Cash Direct Assistance in Cikadu Village, Cikalong District, Tasikmalaya Regency. The theory that became the basis of his analysis of the effectiveness measure of Duncan which consists of 3 variables, namely goal achievement, integration and adaptation. The research method used is descriptive with a qualitative approach, while the data collection techniques are interviews, observation and documentation. The informants are the Village Head, Head of Welfare, Head of Dusun and the beneficiary community. The results showed that the Village Fund Direct Cash Assistance program in Cikadu Village, Cikalong District, Tasikmalaya Regency had been implemented well. However, in the direct cash assistance program, village funds still have to be frequently disseminated to the community so that people who do not receive assistance are not socially jealous and there is a need for increased communication to beneficiary families so that there is no delay in taking aid. Keywords: Effectiveness, Direct Village Fund Cash Assistance